(3QSGdI aj GdUhajIs
(3ChdgG (B:s
(3CeG GdbSe GdKGfi Cda ebGe cd eGFg efgG ai bSe ef GdCbSGe GdYTQI ageG ai bSe GdHOGjGJ GdjbXI hgj CUd ai gPG GdbSe s
(3BNQgG (B:s
(3hTghO GdMb HCSeGFg hUaGJg dGZjQ hai GdMbGFb GdafGA ai GdPGJ eY HbGA GdQSe GdNai GdefhQ GdMb dGZjQ hai GdMbGFb GdafGA ai GdPGJ eY HbGA GdQSe GdNai GdefhQ GdMb GdeTYQ HGdCKjfjI GdeKHJ hdjcf gPG BNQ eG CQOfG EjQGOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B12s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdeLGejYs